(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Permeable paving has been vastly utilized as an alternate to traditional impervious hard surfaces, such as street, parking lots, sidewalk and pedestrian areas. This leads to several rain water management and environmental advantage. Therefore, this study has focused on brief the wide-range of permeable pavement systems These types of permeable pavements have been reviewed in addition to the usefulness of each kind. The results indicated the potential of using such kind in different locations in Iraq is more likely such as Al-Najaf city. Several points of soil investigations have been conducted by previous studies within Al-Najaf city (boundary of Al-Najaf Municipal) prove that Al-Najfa soil is sandy soil. These tested points also demonstrate that the soil characteristics of the city are so suitable for such type of pavement.